Bengal's quest - Leigh, Lora (Leigh, Lora. Novel of the Breeds., 2015)
"He was a shadow, ever shifting and insinuating, able to blend in everywhere and anywhere. The elusive ideal conceived and created by the Genetics Council, he went by just as many names as he had identities--the last one being Gideon. Now calling himself Graeme, he hides in plain sight, terrifyingly close to his goal. A rogue Bengal Breed, he has loyalties to no one but himself. And he has a need for vengeance that surges hot and swift through his veins"--Dust jacket flap.